Prediction of suitable habitat for tundra swans in the Nanji wetland Nature Reserve of Poyang Lake under different water level conditions - Tianwei Fang; Jin Jin; Chao Chen; Li Zhang; Yankuo Li; Chaoyang Li (Ecological Indicators)
It is important to predict the habitat of the migratory bird Cygnus columbianus (tundra swan) at different water levels when generating wetland conservation strategies. Poyang Lake is an important wintering habitat on the migration route of tundra swans. However, the relationship between water level and suitable habitat area is still largely unknown. Therefore, this study employed Maxent to model and predict the five leading environmental factors and their corresponding thresholds affecting the habitat selection of tundra swans. Based on this, the study assessed habitat suitability for tundra swans at different water levels and discussed how water level changes impacted the habitats. Results showed that: (1) Soil humidity, distance to settlements, elevation, wetland landscape type, and NDVI (Normalized difference vegetation index) played dominant roles in the habitat selection of tundra swans. (2) The southwestern lakelets were preferred habitats for tundra swans, whereas the lake branches in the northern region were potentially suitable at various water levels. The eastern area of the study area was more affected by water level changes than the western area. (3) There was a significant correlation between habitat area and water level change.